Comparative analysis of the association between traditional and lipid-related obesity indicators and isolated systolic hypertension - Jian Dong Qian; Xiao Mei Li; Dong Shui Chen; Jian Qin Zhu; Xing Zhen Liu (BMC Cardiovascular Disorders, 2022)
Abstract Background Obesity is a well-known modified risk factor for isolated systolic hypertension (ISH), but evidence is lacking regarding whether the combination of anthropometric and lipid indicators could strengthen their correlation with ISH. Therefore, we compared the association of body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), visceral adiposity index (VAI), lipid accumulation product index (LAP), and cardiometabolic index (CMI) with ISH. Methods A total of 106,248 adults who received routine health screening and did not have diastolic blood pressure ≥ 90 mmHg were recruited in this cross-sectional study. The associations between these indicators and ISH were evaluated using multivariate regression. Results Each standard deviation (SD) increase in traditional obesity indicators (especially WHR and WHtR) had significantly higher multivariate-adjusted odds ratios (ORs) than each SD increase in lipid-related obesity indicators. In addition, multivariate-adjusted ORs for ISH in the third (vs. the first) tertile of traditional obesity indicators were also significantly higher than those of lipid-related indicators. Moreover, traditional obesity indicators exhibited a higher area under the ROC curve for discriminating ISH than lipid-related obesity indicators. Conclusions Traditional obesity indicators were more strongly associated with ISH than lipid-related obesity indicators among Chinese adults.